EVALUASI PENERAPAN STANDAR DAN PEDOMAN BIDANG JALAN DAN JEMBATAN - Anne Kartika Panggabean; Anton Soekiman (Rekayasa Sipil, 2021)
Standardization, as one of the supporting activities for infrastructure development, has an important role in the utilization of resources and all development activities. Until now, 270 SNI documents and 143 road and bridge guidance documents have been published. Standards and guidelines that have been prepared needs to be evaluated for their application. The purpose of this study is to determinate the percentage of use of road dan bridge standards and guidelines, what the factors that influence the use of road and bridge standards and guidelines, and how to take the alternative strategies to improve the implementation standards and guidelines for road and bridge. The methodology used for determinate factors that influence the use of standards dan guidelines for road and bridges is logistic regression analysis, and to find alternative strategy to improve standards and guidelines is use SWOT analysis method. The result of this study is the use of standards and guidelines for road and bridges is still below 50%.  There are 4 factors that influence the use of road and bridge standards and guidelines significantly. The result of SWOT analysis is, the implementation of standards dan guidelines for road and bridges is in quadrant I, which is an advantageous position but need some improvements implementations in the future.